Back to the Future: Whole Blood Resuscitation of the Severely Injured Trauma Patient. (December 2021) - McCoy, Christopher Cameron; Brenner, Megan; Duchesne, Juan; Roberts, Derek; Ferrada, Paula; Horer, Tal; Kauvar, David; Khan, Mansoor; Kirkpatrick, Andrew; Ordonez, Carlos; Perreira, Bruno; Priouzram, Artai; et al.
Abstract : ABSTRACT: Following advances in blood typing and storage, whole blood transfusion became available for the treatment of casualties during World War I. While substantially utilized during World War II and the Korean War, whole blood transfusion declined during the Vietnam War as civilian centers transitioned to blood component therapies. Little evidence supported this shift, and recent conflicts in Iraq and Afghanistan have renewed interest in military and civilian applications of whole blood transfusion. Within the past two decades, civilian trauma centers have begun to study transfusion protocols based upon cold-stored, low anti-A/B titer type O whole blood for the treatment of severely injured civilian trauma patients. Early data suggests equivalent or improved resuscitation and hemostatic markers with whole blood transfusion when compared to balanced blood component therapy. Additional studies are taking place to define the optimal way to utilize low-titer type O whole blood in both prehospital and trauma center resuscitation of bleeding patients.